Literature Review: Impact of Mentoring and Training on Improving the Quality of Nursing Care Documentation - Yuli Triwulandari; Dyah Wiji Puspita Sari; Muh. Abdurrouf; Nopi Nur Khasanah (GLOBAL HEALTH SCIENCE GROUP, 2025)
Quality nursing care documentation is essential to support patient safety, continuity of care, and legal aspects of nursing practice. Mentoring and training are effective strategies to improve nurses' knowledge, skills, and compliance in documenting nursing care accurately and systematically.Objectives: This study aims to analyze the impact of mentoring and training on improving the quality of nursing care documentation. Methods: This study used a literature study approach by reviewing national and international articles published in the period 2019-2025. The articles selected were full-text and open access scientific publications. Literature sources were obtained from three main databases, namely Google Scholar, PubMed, and SciSpace. The search strategy used the PICO (Population, Intervention, Comparison, Outcome) framework with keywords such as